Candida Parapsilosis: a Rare Culprit of Shunt Infection in an Adult - Ersin Ikizoglu; Mert Arslan; Irmak Guzel; Ceren Kizmazoglu; Vildan Avkan Oguz; Burak Sade (Case Reports in Surgery)
Candida parapsilosis is an exceedingly rare cause of ventriculoperitoneal (VP) shunt infection, even in patients who have a history of long-term antibiotic use, immune-compromised newborns, and intensive care unit patients. We hereby report a case of a 53-year-old male who presented with subarachnoid hemorrhage and had a complicated postoperative course due to C. parapsilosis infection, and we discuss the pertinent clinical aspects.